Specific circuit training in young judokas: Effects of rest duration - Baudry, S.; Roux, P. (Research Quarterly for Exercise and Sport, 2009)
Ten adolescent judokas performed circuit training consisting of six 40-s periods of judo exercises separated by 40 s (CT1:1), 120 s (CT1:3), or 200 s (CT1:5) of rest. Heart rate, blood lactate concentration, and the number of repetitions were recorded. Heart rate reached ?180 beats·min-1 at the end of work periods, with slightly lower values for CT1:5. Blood lactate concentration increased until the 6th and 5th work periods for CT1:1 and CT1:3, respectively, whereas the peak value was lower and achieved earlier for CT1:5. Conversely, the number of repetitions was greater during CT1:5. These results suggest that circuit training composed of judo exercises substantially affects aerobic and anaerobic metabolisms, with relative contributions depending on the rest duration.